2017
DOI: 10.1038/s41598-017-05443-5
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA expression profile changes associated with dietary energy in the sheep testis during sexual maturation

Abstract: Spermatogenesis can be affected by nutrition, which operates through normal physiological processes by changing the testicular mass and hormone levels profoundly. However, little is known regarding how testis development is regulated by long noncoding RNA (lncRNA). In this study, we investigated the effects of high-grain (HG) feeding on testis development during sexual maturation mediated by lncRNA. The HG diet group showed an increase in growth hormone (GH), insulin-like growth factor-1 (IGF-1) and testostero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 49 publications
6
26
0
Order By: Relevance
“…Although most of the lncRNAs (n = 4972, 64% of the 7809 lncRNAs with average TPM > 1 in at least one tissue) have idiosyncratic ‘mixed expression’ profiles (see Methods), 1339 lncRNAs (17%) are nevertheless detected at an average TPM > 1 in all 13 tissues (Table S19). Many are enriched in specific tissues, with 904 (12%) lncRNAs exhibiting a testes-specific expression pattern, consistent with a previous study identifying numerous lncRNAs involved in ovine testicular development and spermatogenesis [71].…”
Section: Resultssupporting
confidence: 88%
“…Although most of the lncRNAs (n = 4972, 64% of the 7809 lncRNAs with average TPM > 1 in at least one tissue) have idiosyncratic ‘mixed expression’ profiles (see Methods), 1339 lncRNAs (17%) are nevertheless detected at an average TPM > 1 in all 13 tissues (Table S19). Many are enriched in specific tissues, with 904 (12%) lncRNAs exhibiting a testes-specific expression pattern, consistent with a previous study identifying numerous lncRNAs involved in ovine testicular development and spermatogenesis [71].…”
Section: Resultssupporting
confidence: 88%
“…we found that the expression level of lncRNAs was lower than mRNAs in lamb spleens (Fig. 4 ), which was in agreement with the results from sheep testicular tissues 9 , and the average lengths of lncRNAs and mRNAs in sheep were longer than those in pigs (1,713 bp and 1,983 bp, respectively) 20 . We searched for all the coding genes within the 100-kb flanking regions of the lncRNAs and identified intersecting genes that were significantly co-expressed with the lncRNAs as indicated by Pearson correlation calculations 23 .…”
Section: Discussionsupporting
confidence: 90%
“…We identified 9,082 lncRNAs from tail fat of LFTS, STHS, and TS, and most of them belong to intergenic lncRNAs. LncRNAs from tail fats are relatively abundant compared with these from other tissues, such as 6,924 and 5,602 lncRNAs from muscle and blood samples of Hu sheep, respectively ( Zhang et al, 2017 ; Feng et al, 2018 ). The tail fat lncRNAs also share several typical characters with other mammalian lncRNAs.…”
Section: Discussionmentioning
confidence: 99%